New development: Transparent impact reporting in charity annual reports—benefits, challenges and areas for development. Issue 3 (16th April 2017) - McConville, Danielle
Abstract : The effect of charitable activities on beneficiaries and society is at the heart of what charities exist to do, and stakeholders' reasons for engaging with charities. Reporting publicly and transparently on this impact can form the basis of improved effectiveness, accountability, legitimacy and trust: potentially securing stakeholders' ongoing support and engagement. However, significant challenges to transparent impact reporting are also acknowledged. This article explores these possible benefits, and challenges and highlights areas for development in practice and research.